Analisis Struktural Dan Kearifan Lokal Dalam Legenda “Terjadinya Mado-Mado Nias” Dari Etnis Nias Dan Legenda “Turi-Turin Si Belu Tole” Dari Etnis Karo Serta Relevansinya Dengan Pembelajaran Bahasa Indonesia - Roita Sinaga; Emasta Evayanti Simanjuntak (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The purpose of this research is to analyze the structure and local wisdom in legends in one of the tribes in North Sumatra. The purpose of this study is to analyze the legends of the nias and karo tribes. The method used in this research is descriptive qualitative. The sources of data used in this research are journals, books, and internet sites related to the topics that have been selected. Structural studies include: theme, plot, setting, characters and characterizations, style of language, and point of view. The types of local wisdom include: Welfare and peace. In the legend "The Occurrence of Mado-mado (Marga) Nias" has a social theme about "genealogy, ancestry or origin of the Nias clan". The legend of "Turi-turin Si Beru Tole" has a structural study. The theme in this legend is "marriage". Because in the legend it is told how a woman wanted to get married and was introduced to other people who ended up being married to the village head. Local wisdom contained in the legend here there is peace and prosperity